Effect of smoking and chargrilling on toxic metal(loid) levels in tilapia from the Afram Arm of the Volta Lake. Issue 1 (31st December 2022) - Adherr, Nomolox Solomon Kofi; Dartey, Emmanuel; Dwumfour-Asare, Bismark; Agyapong Asare, Emmanuel; Sarpong, Kofi
ABSTRACT: This study assessed the effect of smoking and chargrilling on arsenic (As), cadmium (Cd), mercury (Hg), and lead (Pb) levels in tilapia from cage farm and wild of the Afram Arm of Lake Volta in Ghana. Method of assessment was an Inductively Coupled Plasma - Mass Spectrometer. Culinary methods did not affect Cd levels in anyway, likewise Pb in cage fish. Wild fish Pb levels decreased significantly (p < 0.05) from raw (0.013 ± 0.004 mg/kg) after smoking (0.0077 ± 0.0007 mg/kg), and chargrilling (0.006 ± 0.0004 mg/kg). Raw As levels (wild: 0.0325 ± 0.0007 mg/kg, cage: 0.0478 ± 0.0009) increased significantly by smoking (wild: 0.064 ± 0.002; cage: 0.0104 ± 0.006). Smoking introduced Hg (0.005mg/kg) in wild samples. Chargrilling significantly increased As levels in cage fish (0.072 ± 0.004). These contaminants were always below the maximum permissible consumption levels. The CR of As was below the threshold (10-4) likewise THQ and HI below (1), hence consuming tilapia from study site either smoked or chargrilled is safe.